2017
DOI: 10.1097/shk.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Inhaled Hydrogen Therapy in a Rat Model of Acute Lung Injury can be Tracked in vivo Using Molecular Imaging

Abstract: Inhaled hydrogen gas (H2) provides protection in rat models of human acute lung injury (ALI). We previously reported that biomarker imaging can detect oxidative stress and endothelial cell death in vivo in a rat model of ALI. Our objective was to evaluate the ability of 99mTc-hexamethylpropyleneamineoxime (HMPAO) and 99mTc-duramycin to track the effectiveness of H2 therapy in vivo in the hyperoxia rat model of ALI. Rats were exposed to room air (normoxia), 98% O2 + 2% N2 (hyperoxia) or 98% O2 + 2% H2 (hyperoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In addition, increased 99m Tc-HMPAO lung uptake has been reported in patients with lung injury resulting from chemotherapy and radiation injury in the absence of perfusion impairment or roentgenographic abnormalities (25) and in patients with diffuse infiltrative lung disease (13). Also, we and others have reported the potential utility of 99m Tc-HMPAO imaging for detecting and monitoring lung injury in preclinical models involving prolonged exposure to high concentrations of oxygen (hyperoxia) (4,5,10), the sepsis mimic lipopolysaccharide (6), and chemotoxic agents (12). These studies revealed increased lung uptake in subjects with subclinical lung injury, suggesting that 99m Tc-HMPAO imaging may be a means for quantitatively detecting lung injury before detection with conventional clinical tools and for assessing the efficacy of novel therapies (5).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, increased 99m Tc-HMPAO lung uptake has been reported in patients with lung injury resulting from chemotherapy and radiation injury in the absence of perfusion impairment or roentgenographic abnormalities (25) and in patients with diffuse infiltrative lung disease (13). Also, we and others have reported the potential utility of 99m Tc-HMPAO imaging for detecting and monitoring lung injury in preclinical models involving prolonged exposure to high concentrations of oxygen (hyperoxia) (4,5,10), the sepsis mimic lipopolysaccharide (6), and chemotoxic agents (12). These studies revealed increased lung uptake in subjects with subclinical lung injury, suggesting that 99m Tc-HMPAO imaging may be a means for quantitatively detecting lung injury before detection with conventional clinical tools and for assessing the efficacy of novel therapies (5).…”
Section: Introductionmentioning
confidence: 89%
“…Also, we and others have reported the potential utility of 99m Tc-HMPAO imaging for detecting and monitoring lung injury in preclinical models involving prolonged exposure to high concentrations of oxygen (hyperoxia) (4,5,10), the sepsis mimic lipopolysaccharide (6), and chemotoxic agents (12). These studies revealed increased lung uptake in subjects with subclinical lung injury, suggesting that 99m Tc-HMPAO imaging may be a means for quantitatively detecting lung injury before detection with conventional clinical tools and for assessing the efficacy of novel therapies (5).…”
Section: Introductionmentioning
confidence: 95%
“…As previously described [ 19 ], mitochondrial membrane potential (ΔΨ m ) studies were performed at room temperature (23°C) using a Photon Technology International (PTI) QuantaMaster spectrofluorometer (HORIBA Scientific, Edison, New Jersey) that monitored and recorded the R123 fluorescent signal (503/527 nm excitation/emission wavelength) continuously over time. Briefly, a cuvette containing 1 ml of the respiration buffer (pH 7.2), R123 (200 nM), and either pyruvate (10 mM) + malate (5 mM) or succinate (7 mM) as respiratory substrate was placed in the cuvette holder of the spectrofluorometer.…”
Section: Methodsmentioning
confidence: 99%
“…So far, the preventive and therapeutic effects of molecular hydrogen for various lung diseases, such as ALI, chronic obstructive pulmonary disease, asthma, and pulmonary arterial hypertension, have been extensively investigated (Kishimoto et al 2015;Audi et al 2017;Wang et al 2020). China's National Health Commission (7th trial ed NHC: Bejing, 2020) and the Chinese Center for Disease Control and Prevention (6th ed.…”
Section: Introductionmentioning
confidence: 99%